Physical Condition Profile of Male Archery Athletes in Bengkalis Regency - Fahrul Rizal (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aimed to determine the physical condition level of male archery athletes in Bengkalis Regency by assessing several physical fitness components, including muscular strength, muscular endurance, and cardiovascular endurance, as the basis for evaluating athlete readiness and supporting future training programs. Methodology: This study employed a descriptive quantitative research design involving 12 male archery athletes from Bengkalis Regency selected through total sampling. Data were collected using Leg Dynamometer, Hand Dynamometer, Back Dynamometer, Pull-Up Test, Wall Squat Test, and the 15-Minute Balke Run Test (VO₂Max). Data analysis utilized descriptive statistics and percentage calculations based on established physical fitness norms. Main Findings: The findings revealed that the overall physical condition of male archery athletes in Bengkalis Regency was categorized as poor. Most athletes demonstrated inadequate performance in muscular strength, muscular endurance, and cardiovascular endurance components. The overall assessment indicated that 58.33% of the athletes were classified within the poor physical condition category, highlighting the need for systematic physical conditioning programs. Novelty/Originality of this study: This study provides a comprehensive physical condition profile of regional archery athletes by simultaneously evaluating six essential physical fitness components relevant to archery performance. The findings offer practical baseline data for coaches and sports organizations in designing evidence-based training programs and contribute to the limited literature on physical condition assessment among Indonesian regional archery athletes.